Gender Dynamics in Muslim Families with Wives as the Main Breadwinner (A Study in Benda Village Sirampog Subdistrict Brebes Regency) - Akso Yanto; Misbahul Huda (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2025)
This study analyses the role of wives as the main breadwinners in families in Benda Village, Sirampog Subdistrict, Brebes Regency, using a gender perspective. This phenomenon has emerged due to economic factors, whereby husbands' incomes are no longer sufficient to meet family needs. Using a qualitative approach and case studies in Benda Village, this study examines how this role is played and analyses it through gender theory, specifically Sara Longwe's analytical model. The results show that although the role of wives as primary breadwinners has significantly improved the family's welfare and access to resources, this does not necessarily go hand in hand with increased participation, awareness, and equal control. This new role is based more on internal family agreements to meet economic needs than on the full adoption of gender equality values. These findings confirm that changes in economic roles are not always followed by changes in power structures and decision-making within the household.